Construction of pillar[4]arene[1]quinone–1,10-dibromodecane pseudorotaxanes in solution and in the solid state - Sheng, Xinru; Li, Errui; Huang, Feihe (Beilstein Journal of Organic Chemistry, 2020)
We report novel pseudorotaxanes based on the complexation between pillar[4]arene[1]quinone and 1,10-dibromodecane. The complexation is found to have a 1:1 host–guest complexation stoichiometry in chloroform but a 2:1 host–guest complexation stoichiometry in the solid state. From single crystal X-ray diffraction, the linear guest molecules thread into cyclic pillar[4]arene[1]quinone host molecules in the solid state, stabilized by CH∙∙∙π interactions and hydrogen bonds. The bromine atoms at the periphery of the guest molecule provide convenience for the further capping of the pseudorotaxanes to construct rotaxanes.
Keywords: host–guest chemistry; pillar[4]arene[1]quinones; pillararenes; pseudorotaxanes; supramolecular chemistry

(untitled) - Sun, Q.-F.; Iwasa, J.; Ogawa, D.; Ishido, Y.; Sato, S.; Ozeki, T.; Sei, Y.; Yamaguchi, K.; Fujita, M. (Science, 2010)

(untitled) - Aida, T.; Meijer, E. W.; Stupp, S. I. (Science, 2012)

(untitled) - Chifotides, H. T.; Dunbar, K. R. (Acc. Chem. Res., 2013)

(untitled) - Mattia, E.; Otto, S. (Nat. Nanotechnol., 2015)

(untitled) - Kaphan, D. M.; Levin, M. D.; Bergman, R. G.; Raymond, K. N.; Toste, F. D. (Science, 2015)

(untitled) - Zhang, X.; Wang, C. (Chem. Soc. Rev., 2011)

(untitled) - Mura, S.; Nicolas, J.; Couvreur, P. (Nat. Mater., 2013)

(untitled) - Wang, X.; Han, Y.; Liu, Y.; Zou, G.; Gao, Z.; Wang, F. (Angew. Chem., Int. Ed., 2017)

(untitled) - Han, Y.; Tian, Y.; Li, Z.; Wang, F. (Chem. Soc. Rev., 2018)

(untitled) - Liu, Y.; Zhao, W.; Chen, C.-H.; Flood, A. H. (Science, 2019)

(untitled) - Zhang, Z.; Cheng, L.; Zhao, J.; Wang, L.; Liu, K.; Yu, W.; Yan, X. (Angew. Chem., Int. Ed., 2020)

(untitled) - Niu, Z.; Gibson, H. W. (Chem. Rev., 2009)

(untitled) - Niu, Z.; Huang, F.; Gibson, H. W. (J. Am. Chem. Soc., 2011)

(untitled) - Guo, D.-S.; Wang, K.; Wang, Y.-X.; Liu, Y. (J. Am. Chem. Soc., 2012)

(untitled) - Langton, M. J.; Beer, P. D. (Acc. Chem. Res., 2014)

(untitled) - Qu, D.-H.; Wang, Q.-C.; Zhang, Q.-W.; Ma, X.; Tian, H. (Chem. Rev., 2015)

(untitled) - Li, S.-H.; Zhang, H.-Y.; Xu, X.; Liu, Y. (Nat. Commun., 2015)

(untitled) - Eichstaedt, K.; Jaramillo-Garcia, J.; Leigh, D. A.; Marcos, V.; Pisano, S.; Singleton, T. A. (J. Am. Chem. Soc., 2017)

(untitled) - De Bo, G.; Dolphijn, G.; McTernan, C. T.; Leigh, D. A. (J. Am. Chem. Soc., 2017)

(untitled) - Wang, Y.; Sun, J.; Liu, Z.; Nassar, M. S.; Botros, Y. Y.; Stoddart, J. F. (Chem. Sci., 2017)

(untitled) - Lewis, J. E. M.; Beer, P. D.; Loeb, S. J.; Goldup, S. M. (Chem. Soc. Rev., 2017)

(untitled) - Roberts, D. A.; Pilgrim, B. S.; Nitschke, J. R. (Chem. Soc. Rev., 2018)

(untitled) - Li, G.; Wang, L.; Wu, L.; Guo, Z.; Zhao, J.; Liu, Y.; Bai, R.; Yan, X. (J. Am. Chem. Soc., 2020)

(untitled) - Ogoshi, T.; Kanai, S.; Fujinami, S.; Yamagishi, T.-a.; Nakamoto, Y. (J. Am. Chem. Soc., 2008)

(untitled) - Cao, D.; Kou, Y.; Liang, J.; Chen, Z.; Wang, L.; Meier, H. (Angew. Chem., Int. Ed., 2009)

(untitled) - Xue, M.; Yang, Y.; Chi, X.; Yan, X.; Huang, F. (Chem. Rev., 2015)

(untitled) - Ogoshi, T.; Yamagishi, T.-a.; Nakamoto, Y. (Chem. Rev., 2016)

(untitled) - Han, C.; Zhao, D.; Li, H.; Wang, H.; Huang, X.; Sun, D. (ChemistrySelect, 2018)

(untitled) - Jie, K.; Zhou, Y.; Li, E.; Huang, F. (Acc. Chem. Res., 2018)

(untitled) - Si, W.; Chen, L.; Hu, X.-B.; Tang, G.; Chen, Z.; Hou, J.-L.; Li, Z.-T. (Angew. Chem., Int. Ed., 2011)

(untitled) - Chen, Y.; Cao, D.; Wang, L.; He, M.; Zhou, L.; Schollmeyer, D.; Meier, H. (Chem. – Eur. J., 2013)

(untitled) - Xia, B.; Xue, M. (Chem. Commun., 2014)

(untitled) - Chen, H.; Fan, J.; Hu, X.; Ma, J.; Wang, S.; Li, J.; Yu, Y.; Jia, X.; Li, C. (Chem. Sci., 2015)

(untitled) - Sun, Y.; Fu, W.; Chen, C.; Wang, J.; Yao, Y. (Chem. Commun., 2017)

(untitled) - Du, X.-S.; Wang, C.-Y.; Jia, Q.; Deng, R.; Tian, H.-S.; Zhang, H.-Y.; Meguellati, K.; Yang, Y.-W. (Chem. Commun., 2017)

(untitled) - Zhang, Z.; Xia, B.; Han, C.; Yu, Y.; Huang, F. (Org. Lett., 2010)

(untitled) - Zhang, Z.; Luo, Y.; Chen, J.; Dong, S.; Yu, Y.; Ma, Z.; Huang, F. (Angew. Chem., Int. Ed., 2011)

(untitled) - Ogoshi, T.; Demachi, K.; Kitajima, K.; Yamagishi, T.-a. (Chem. Commun., 2011)

(untitled) - Hu, X.-B.; Chen, Z.; Tang, G.; Hou, J.-L.; Li, Z.-T. (J. Am. Chem. Soc., 2012)

(untitled) - Ni, M.; Hu, X.-Y.; Jiang, J.; Wang, L. (Chem. Commun., 2014)

(untitled) - Sun, C.-L.; Xu, J.-F.; Chen, Y.-Z.; Niu, L.-Y.; Wu, L.-Z.; Tung, C.-H.; Yang, Q.-Z. (Chin. Chem. Lett., 2015)

(untitled) - Ma, J.; Meng, Q.; Hu, X.; Li, B.; Ma, S.; Hu, B.; Li, J.; Jia, X.; Li, C. (Org. Lett., 2016)

(untitled) - Li, B.; Meng, Z.; Li, Q.; Huang, X.; Kang, Z.; Dong, H.; Chen, J.; Sun, J.; Dong, Y.; Li, J.; Jia, X.; Sessler, J. L.; et al. (Chem. Sci., 2017)

(untitled) - Han, C.; Zhang, Z.; Yu, G.; Huang, F. (Chem. Commun., 2012)

(untitled) - Ogoshi, T.; Yamafuji, D.; Kotera, D.; Aoki, T.; Fujinami, S.; Yamagishi, T.-a. (J. Org. Chem., 2012)